Peroxiredoxin 5 modulates immune response in Drosophila - Radyuk, Svetlana N. (2010)
BACKGROUND: Peroxiredoxins are redox-sensing enzymes with multiple cellular functions. Previously, we reported on the potent antioxidant function of Drosophila peroxiredoxin 5 (dPrx5). Studies with mammalian and human cells suggest that peroxiredoxins can modulate immune-related signaling. METHODS: Survivorship studies and bacteriological analysis were used to determine resistance of flies to fungal and bacterial infections. RT-PCR and immunoblot analyses determined expression of dPrx5 and immunity factors in response to bacterial challenge. Double mutants for dprx5 gene and genes comprising the Imd/Relish and dTak1/Basket branches of the immune signaling pathways were used in epistatic analysis. RESULTS: The dprx5 mutant flies were more resistant to bacterial infection than controls, while flies overexpressing dPrx5 were more susceptible. The enhanced resistance to bacteria was accompanied by rapid induction of the Imd-dependent antimicrobial peptides, phosphorylation of the JNK kinase Basket and altered transcriptional profiling of the transient response genes, puckered, ets21C and relish, while the opposite effects were observed in flies over-expressing dPrx5. Epistatic analysis of double mutants, using attacin D and Puckered as read outs of activation of the Imd and JNK pathways, implicated dPrx5 function in the control of the dTak1-JNK arm of immune signaling. CONCLUSIONS: Differential effects on fly survivorship suggested a trade-off between the antioxidant and immune functions of dPrx5. Molecular and epistatic analyses identified dPrx5 as a negative regulator in the dTak1-JNK arm of immune signaling. GENERAL SIGNIFICANCE: Our findings suggest that peroxiredoxins play an important modulatory role in the Drosophila immune response.